Expression of Immune Checkpoint Receptors in Placentae With Infectious and Non-Infectious Chronic Villitis - Shahi, Maryam; Mamber Czeresnia, Ricardo; Cheek, E. Heidi; Quinton, Reade A.; Chakraborty, Rana; Enninga, Elizabeth Ann L. (Frontiers in Immunology, 2021)
Pregnancy is an immunological paradox whereby maternal immunity accepts a genetically unique fetus (or fetuses), while maintaining protective innate and adaptive responses to infectious pathogens. This close contact between the genetically diverse mother and fetus requires numerous mechanisms of immune tolerance initiated by trophoblast cell signals. However, in a placental condition known as villitis of unknown etiology (VUE), there appears to be a breakdown in this tolerance allowing maternal cytotoxic T-cells to traffic into the placenta to destroy fetal villi. VUE is associated with several gestational complications and an increased risk of recurrence in a subsequent pregnancy, making it a significant obstetrical diagnosis. The cause of VUE remains unclear, but dysfunctional signaling through immune checkpoint pathways, which have a critical role in blunting immune responses, may play an important role. Therefore, using placental tissue from normal pregnancy (n=8), VUE (n=8) and cytomegalovirus (CMV) infected placentae (n=4), we aimed to identify differences in programmed cell death 1 (PD-1), programmed death ligand-1 (PD-L1), LAG3 and CTLA4 expression between these etiologies by immunohistochemistry (IHC). Results demonstrated significantly lower expression of PD-L1 on trophoblast cells from VUE placentae compared to control and CMV infection. Additionally, we observed significantly higher counts of PD-1+ (>100 cells/image) and LAG3+ (0-120 cells/image) cells infiltrating into the villi during VUE compared to infection and control. Minimal CTLA4 staining was observed in all placentae, with only a few Hofbauer cells staining positive. Together, this suggests that a loss of tolerance through immune checkpoint signaling may be an important mechanism leading to the activation and trafficking of maternal cells into fetal villi during VUE. Further mechanistic studies are warranted to understand possible allograft rejection more clearly and in developing effective strategies to prevent this condition from occurring in utero.